Comparison of live born twins conceived by artificial reproductive technologies to naturally conceived twins. (18th April 2012) - Shetty, M; Eason, J
Abstract : Aims: To compare the neonatal outcome of live born twins conceived by artificial reproductive technologies (ART) to naturally conceived (NC) twins. Methods: All live twins born in the maternity centre between Jan 2007 to Dec 2008 were studied retrospectively. Analysis of ART twins to NC twins and to NC dichorionic diamniotic (DCDA) twins were done using chi-square tests or Fisher's exact test where appropriate. Results: Live twin deliveries were 318 constituting 3.4% of the total live deliveries. Among the NC twins, 177 twins were DCDA, 70 twins were monochorionic diamniotic (MCDA) and in other 8 twins zygosity was not documented. All ART twins were DCDA. ART twins had increased maternal age and more of para 0 mother than the NC twins. Gestational age at birth and birth weight in each group showed no statistical significant difference. 2 of ART twins, 4 of NC DCDA twins and 9 of the NC twins died. All the twins who died were of extreme prematurity with less than 28 weeks of gestation. No twins in the ART group had major congenital anomaly or morbidity at the time of discharge. Number of twins admitted and level of care received in each group had no statistical significant difference. Conclusions: Evidence on neonatal outcomes of twins following ART compared with NC twins is controversial, though more recent studies have shown similar outcome which our observational study corroborates with.